Lesbian literature a third world feminist perspective - Moraga, Cherrie; Smith, Barbara (The Radical Teacher, 2014)
"A Baseline From Which to Build a Political Understanding: The Background and Goals of the Course."Barbara Smith: I'd taught Black women's literature, interdisciplinary courses on Black women and talked about Lesbianism as an "out" lesbian in my "Introduction to Women's Studies" courses, but I really wanted to do a Lesbian lit course. Lesbian literature had never been offered by the Women's Studies program at the University of Massachusetts in Boston, although the program is almost ten years old. There was a gay literature course that had been co-taught by a gay man and a lesbian, but its orientation was quite a bit different from what I had in mind.
Keywords: approches et analyses; féminisme décolonial; histoire et politique; lesbianisme; littérature; personnes lesbiennes; pédagogie; ressource en ligne; thématiques

All the women are white, all the Blacks are men, but some of us are brave: Black women's studies - Hull, Gloria T.; Scott, Patricia Bell; Smith, Barbara (The Feminist Press at the City University of New York, 2015)
This ground-breaking collection provides hours of enjoyment for the general reader and a wealth of materials needed to develop course units on black women; political theory, literary essays on major writers, guidelines for consciousness-raising about racism, and surveys of black women's contributions to the blues. "Important and innovative
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem7000; femmes* afro-américaines; féminismes noirs; intersectionnalité; lit3220; premier cycle; périodes historiques; racisme; régions géographiques; savoirs; sexisme; systèmes d'oppressions; états-unis